Should I Move? The Benefits and Costs of Spatial Mobility for Different Groups of the Roma Population - Ember, Zsolt; Huszti, Éva; Lénárt, Imre (European Journal of Mental Health, 2023)
Introduction: Moving away can be motivated by a multitude of factors, just as the reasons for not moving away might be different. The individual’s social situation greatly determines the chance of turning their life situation around through moving away.Aims: We investigated the factors that affected the representatives of the three Roma groups researched here (Romungro, Vlach, Boyash) in their moving in the past and in their intentions to move in the future.Methods: A SEM model was developed (N = 570) to analyze the differences between previous movers and non-movers in well-being, socioeconomic status, and social network. We also investigated the effect of the above variables on the intention to move. Data were collected via the “snowball method”.Results: Out of the Vlachs, those who had moved in the past have significantly fewer confidant relatives (p = .021) and also know significantly fewer people pursuing high-prestige vocations (p = .003), moreover, the fewer people pursuing moderate-prestige vocations they know, the more they would like to move away from their present residence (p = .031). Regarding the Boyash, the more favorable their socio-economic situation, the more they would like to move away (p = .007); while regarding the Romungro, the low level of their mental wellbeing (p = .019) and the relatively high number of their confidant relatives constitutes (p = .017) the incentive to change their residence.Conclusions: The spatially mobile Roma who had moved before possess fewer confidant relatives and weak ties. The individual factors connect to the different Roma groups’ moving intentions to various extents.